[OP.LB01.06] EFFECTIVENESS OF A COMPREHENSIVE HEALTH PROMOTION STRATEGY IN WORKERS WITH HIGH CARDIOVASCULAR RISK. (September 2016) - Calvo-bonacho, E.; Catalina-romero, C.; Sainz-gutiérrez, J.C.; Cabrera-sierra, M.; Quevedo-aguado, L.; Fernández-labandera, C.; Brotons, C.; Ruilope, L.M.
Abstract : Objective: To assess the impact of the implementation of a comprehensive health promotion strategy in controlling cardiovascular risk factors (CVRF), among workers at high risk of cardiovascular disease (CVD). Design and method: CVRF were assessed in an occupational cohort of 8, 975 workers with high CVR (SCORE > = 5%) from the ICARIA Study. CVRF and CVR were assessed again after a 1-year follow-up (365 ± 90 days). All workers were informed about their CVR, were given recommendations regarding CVRF control and changes in their lifestyle while they participated in a Comprehensive Health Promotion Strategy provided by their Mutual Insurance Company. Joint European Societies' guidelines on cardiovascular disease prevention were followed in order to evaluate CVRF control. McNemar's test for paired data was used to compare differences in CVRF between baseline and follow-up. Results: 89.3% of participants were men (mean age 51.1 ± 32.3 years-old). The percentage of patients with prior CVD was 8.2%. After a 1-year follow-up, 46.4% of workers at high CVR and no prior CVD decreased their CVR to less than 5%. Improvements in CVRF control were observed: increasing percentage of non-smokers (+3.9%; p < 0.001), of workers with blood pressure < 140/90 mmHg (+13.0%; p < 0.001), total-cholesterol < 190 mg/dl (+5.9%; p < 0.001), LDL-cholesterol <100 mg/dl [high CVR] / <70 mg/dl [very high CVR] (+3.9%; p < 0.001), and triglycerides <150 mg/dl (+2.6%; p < 0.001). In contrast, a decrease in the percentage of workers with HDL-cholesterol >40 mg/dl [men] / >45 mg/dl [women] (-2.1%; p < 0.001) was observed. No significant differences were detected in the percentage of workers with glycaemia <126 mg/dl (p = 0.537), body mass index <25 Kg/m2 (p = 0.967), or waist circumference <102 cm [men] / <88 cm [women] (p = 0.232). Conclusions: A comprehensive health promotion strategy at the workplace is effective in improving control of CVRF in workers at high risk of cardiovascular disease. This achievement could complement the work done by general practitioners and nurses in their consultation visits. Further efforts are necessary to improve weight reduction.